Analisis Biaya Produksi dengan Pendekatan Activity Based Costing (ABC) (Studi Kasus: UMKM Keripik Singkong di Pasuruan) - Riski, Lutfir; Sulistyowati, Enik (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the production costs of cassava chips in MSMEs in Grati District, Pasuruan Regency, using the Activity Based Costing (ABC) approach. The ABC method is chosen because it can allocate costs accurately based on activities in the production process, thus providing a more realistic cost picture compared to traditional methods. Data were obtained through direct observation, interviews with MSME actors, and documentation of raw material costs, labor, and production overhead. The analysis results show that the ABC method can identify the main cost-consuming activities, such as raw material processing, frying, and packaging. The cost of goods sold (COGS) per unit using the ABC method is IDR 1,866, which is lower than the traditional method of IDR 3,363, with a saving of 44.52%. This understanding helps MSMEs control and optimize resources, improving production cost efficiency. The study also provides strategic recommendations for setting competitive selling prices and increasing business profitability. In conclusion, the ABC method effectively assists MSMEs in managing production costs accurately and transparently.